Descriptive analysis and genetic dissimilarity between accesses of acerola trees - Magalhães, D. S.; Rufini, J. C. M.; Fagundes, M. C. P.; Albuquerque, A. S.; Ramos, M. C. P. (Scientific Electronic Archives, 2018)
Among the fruits with economic and social potential in Brazil, has acerola. The country stands out as a world producer of this fruit, presenting ideal conditions for its cultivation. However, most of the existing orchards are lacking in fruit quality characteristics, especially for processing industries, demanding studies in the field of genetic improvement aimed at new varieties that concentrate desirable characteristics of the crop. The objective of this work was to carry out a descriptive analysis and to determine the genetic dissimilarity of the accesses of cherry trees in the municipality of Sete Lagoas, Minas Gerias. The experiment was conducted in a completely randomized design, with four replicates and 20 accessions of acerolaÂ trees. For the description of the accessions, the means, the standard deviation and the coefficient of variation of the studied variables were used. The character correlation study was determined by the Pearson method and genetic dissimilarity was analyzed by Euclidean Distance and the grouping by the Neighboring Neighbor Hierarchical Method and the Tocher Optimization Method. According to the results of Mean Euclidean Distances between pairs, accesses 6 and 8 presented greater genetic dissimilarity. The Tocher method allowed the formation of seven groups of genotypes. Genotype 8 presented the best averages for most of the analyzed characters, and may be indicated for crossing with accesses of distinct groups that also present good averages of the most interesting characteristics, such as accesses 6 and 12.